Direct diode laser cladding of Inconel 625/WC composite coatings - Janicki, Damian (Strojniški vestnik, 2016)
Metal matrix composite coatings, composed of Inconel 625 alloy and tungsten carbide (WC), have been produced by laser cladding using a high power direct diode laser with a rectangular laser beam spot and a top-hat beam profile. The primary goal of the investigation was to understand the role of the shape of WC particles and the heat input level on the quality of the composite coating system used, especially on its erosion behaviour. The results indicated that angular WC particles are more susceptible to dissolution in the molten pool than spherical. However, the composite coatings containing angular WC particles exhibited significantly higher erosion resistance than those with spherical WC for both normal and oblique impacts. This is directly attributed to the excellent mechanical interlocking of the angular WC in the matrix. The WC/matrix interfacial decohesion has been observed in the coatings containing spherical WC at the oblique impact.
Keywords: direktni diodni laser; erozijska obraba; Inconel 625; kompozitna prevleka s kovinskim matriksom; lasersko navarjanje